High-Stepping Cross-Country Athlete: A Unique Case of Foot Drop and a Novel Treatment Approach. Issue 5 (September 2017) - Tabor, Melissa; Emerson, Blaze; Drucker, Rebecca; Brunk, Eric
Abstract : Ganglion cyst-induced peroneal neuropathy successfully treated with ultrasound guided cyst aspiration and nerve hydrodissection.